Thoracoscopic detection of thoracic ducts after ultrasound‐guided intrahepatic injection of indocyanine green detected by near‐infrared fluorescence and methylene blue in dogs. (23rd July 2021) - Korpita, Megan F.; Mayhew, Philipp D.; Steffey, Michele A.; Balsa, Ingrid M.; Giuffrida, Michelle A.; Chohan, Amandeep S.; Johnson, Eric G.
Abstract: Objective: To describe and compare onset and intensity of thoracic duct (TD) coloration in healthy dogs after intrahepatic injection of either indocyanine green (ICG) visualized by intraoperative near‐infrared fluorescence lymphography (NIRFL) or direct thoracoscopic visualization of methylene blue dye (MB). Study Design: Prospective study. Animals: Healthy adult Beagle dogs ( n  = 5). Methods: All dogs had biochemical panels and complete blood counts preoperatively. Computed tomography lymphography (CTL) was performed prior to a standard 3‐port thoracoscopic approach. A mixture of MB and ICG was injected by ultrasound‐guided percutaneous injection into right or left‐sided hepatic lobes. Data collected included dose of contrast agent (MB vs. ICG), injection site, timing, and quality of operative TD identification. Potential hepatic injury was assessed by repeat laboratory evaluation and abdominal ultrasound 14 days postoperatively. Results: Preoperative CTL provided a diagnostic study in 5/5 dogs. After intrahepatic injection of combined dyes, NIRFL allowed visualization of TDs in 5/5 dogs, but MB did not result in visible TD coloration in any dog. Intrahepatic injection of ICG achieved successful NIRFL in a median time of 6 minutes and persisted for the 20 minute observation period in all five dogs. All dogs recovered without complication and were subsequently adopted. Conclusion: NIRFL of the TD can be achieved with intraoperative hepatic injection of ICG. Intrahepatic injection of MB did not result in visible TD coloration. Clinical Significance: Hepatic intra‐parenchymal injection is a reliable alternative portal into the TD system for intraoperative visualization of TD anatomy using ICG in dogs.